Primary modular straight stem cemented prosthetic replacement for unstable, comminuted intertrochanteric fracture in the elderly with severe osteoporosis - Pillai, Manju G. (International Journal of Research in Orthopaedics, 2019)
Background: The increasing number of hip fractures in the elderly, with the subset of unstable, comminuted intertrochanteric hip fractures is extremely relevant as the treatment is hampered by unsuccessful fixations and high complication rates. Osteoporosis and fracture geometry are two factors responsible for the failure of fixation in such fractures, upon which the surgeon has no control. Hence newer methods of fixation or treatment have to be opted for. The objective of the study was to evaluate the functional outcome of primary modular cemented prosthetic replacement for unstable, osteoporotic intertrochanteric fractures in a selected group of patients. Methods: A total of 34 patients with type II and type III unstable intertrochanteric fractures were treated with primary modular cemented bipolar prosthesis and followed up in Pushpagiri Institute of Medical Sciences and Research Centre, Tiruvalla. Results: After surgery 94.12% patients regained walking capacity. The functional outcome at the time of discharge was fair to excellent in 88.24% of cases. The complications were few and the major benefit was early ambulation of patients and return to pre-fracture level of activity. Conclusions: Primary modular bipolar straight stem cemented prosthetic replacement is probably the best option for treatment in previously independently ambulant, elderly osteoporotic patients with unstable, comminuted intertrochanteric fracture of femur.